An examination of equity market linkages and benefits of international portfolio diversification - Fitzgerald, Keith (Trinity College (Dublin, Ireland). Trinity Business School, 2016)
The extent of global equity market integration in a post-crisis world is an important consideration for investors and academics alike. While market integration has received substantial attention in the extant literature, until now, relatively little has been done to characterise world equity market linkages beyond the global crisis. Modern portfolio theory informs us that a low return correlation between national stock markets should motivate diversification strategy (Markowitz, 1952; Gmbel 1968). It stands to reason that diversification benefits are greatest when markets are not positively correlated; if markets respond symmetrically to shocks, diversification benefits may not exist when they are needed most. Furthermore, the trend toward trade and capital market liberalisation, as well as monetary policy coordination, has led to an increasingly globalised and interdependent world (Goetzmann et ah, 2005; Coelho et ah, 2007; Quinn and Voth, 2008), with equity market integration posing a direct challenge to the international diversification of portfolios. The global nature of the recent crisis mandates an analysis across a complete set of developed and emerging markets that assesses, in explicit detail, the ramifications of the crisis period for global linkages. This thesis examines equity market linkages across a sample of forty-six markets between January 1995 and December 2013.
Keywords: Business, Ph.D.; PhD Trinity College Dublin, 2016